2016
DOI: 10.3389/fmicb.2016.00110
|View full text |Cite
|
Sign up to set email alerts
|

In silico Analysis of HIV-1 Env-gp120 Reveals Structural Bases for Viral Adaptation in Growth-Restrictive Cells

Abstract: Variable V1/V2 and V3 loops on human immunodeficiency virus type 1 (HIV-1) envelope-gp120 core play key roles in modulating viral competence to recognize two infection receptors, CD4 and chemokine-receptors. However, molecular bases for the modulation largely remain unclear. To address these issues, we constructed structural models for a full-length gp120 in CD4-free and -bound states. The models showed topologies of gp120 surface loop that agree with those in reported structural data. Molecular dynamics simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 76 publications
(176 reference statements)
4
32
0
Order By: Relevance
“…(32,33), closed BG505 trimer (PDB ID code 5FYJ) (10,19), and molecular dynamics model of repositioned V1V2 in full-length CD4-bound gp120 (21). β-strand nomenclature in V1V2 is the same as in ref.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(32,33), closed BG505 trimer (PDB ID code 5FYJ) (10,19), and molecular dynamics model of repositioned V1V2 in full-length CD4-bound gp120 (21). β-strand nomenclature in V1V2 is the same as in ref.…”
Section: Discussionmentioning
confidence: 99%
“…The details of V1V2 rearrangements in the open structure of HIV-1 Env trimer have not been addressed: The V1V2 loops were not localized in the Env trimer used in a cryo-EM single particle structure of an open KNH1144 SOSIP bound to the coreceptormimicking antibody 17b (7) or in lower-resolution cryoelectron tomography structures of CD4-bound open Env trimers on virions (4,7). However, computational modeling suggested displacement of V1V2 toward CD4 in CD4-bound Env structures (20,21), consistent with earlier studies demonstrating involvement of V1V2 in the induction of the epitopes of coreceptor mimic/CD4-induced antibodies such as 17b (22).…”
mentioning
confidence: 99%
“…Glycosylated HA trimer models in a ligand-free state were subjected to MD simulation essentially as described for simulations of HIV-1 gp120 (Yokoyama et al, 2016). MD simulations were performed by the PMEMD (Particle Mesh Ewald Molecular Dynamics) module in the AMBER 14 program package (Case et al, 2014), employing the Amber ff99SB-ILDN force field, a protein force field with improved side-chain torsion potentials (Lindorff-Larsen et al, 2010), the GLYCAM06 force field, a biomolecular force field for glycans (Kirschner et al, 2008), and the TIP3P water model for simulations of aqueous solutions (Jorgensen et al, 1983).…”
Section: Methodsmentioning
confidence: 99%
“…The MD simulations have been used to disclose the structural basis of the adaptation and evolution of the highly mutable human immunodeficiency virus (HIV). This includes elucidation of the HIV structural changes associated with the phenotypic changes in viral neutralization sensitivity and receptor tropism (Naganawa et al, 2008; Yokoyama et al, 2012, 2016; Kuwata et al, 2013), viral sensitivity to antiviral protein (Miyamoto et al, 2012), viral drug sensitivity (Yuan et al, 2013), viral growth in non-natural host cells (Yokoyama et al, 2016), and viral sensitivities to antibodies by drug-resistance mutations (Alam et al, 2016; Hikichi et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…1). We recently showed that a mutant virus carrying a growth-enhancing mutation G310R exhibited distinct sensitivity to CCR5 antagonist TAK-779 from that of a mutant virus bearing S304G (19). Fig.…”
Section: Virological Characterization Of Hiv-1rmt Clonesmentioning
confidence: 96%